Optimization of electrospinning process to fabricate core/shell structure of magnetic nanofibers via ''RSM'' - Ahmadipourroudposht, Mohaddeseh (2013)
Magnetic nanostructure properties compare to their massive form recently makes them as an attraction for further research. Magnetic nanofibers are potentially useful for substrate bone regeneration, high data storage and intelligent protective shield due to immediate reaction to external field. Magnetic nanoparticles agglomeration is an obstacle in preparation a fancy morphology of magnetic nanofibers. Encapsulating the magnetic particles with an organic materials solve this limitation partially. Co-axial electrospinning is a fashionable method of Core/shell structure nanofibers fabrication. Fabricated fibers have an ultra-fine quality and porosity property with nano size diameter (~ 20 to1000nm) compare to other methods. In this study to fabricate magnetic nanofibers polyvinyl alcohol (PVA) utilized as shelter for (?-Fe2O3) magnetic particles suspension. Previously a full factorial design was conducted to evaluate the performance and factor screening of electrospinning process. That research determines flow rate and voltage and interaction between these two factors are significantly affected on output which is diameter distribution but the two other factors as distance between needle and collector and drum collector rotating speed affect are insignificant. The optimum diameter refer to previous experiments was 280 nm. In this research it is supposed to optimize the diameter distribution refer to those two significant factors via response surface methodology (RSM). Optimization in this case refers to minimizing the diameter for improving the tensile strength for its possible use in bullet proof vest